Tuning of renewable sponge-like polyurethane physical-chemical and morphological properties using the pullulan as a reactive filler - Maia, Lana S.; de Bomfim, Anne Shayene C. [UNESP]; de Oliveira, Daniel M. [UNESP]; Pinhati, Fernanda R.; da Conceição, Monique O. T.; Barud, Hernane S.; Medeiros, Simone A.; Rosa, Derval S.; Mulinari, Daniella R. (Wiley, 2023)
This study aimed to evaluate the effect of pullulan (Pull) on a renewable polyurethane sponge-like scaffold synthesized from the Pull mixture with the castor oil-based polyol and the prepolymer using the situ foaming method. The Pull contents on the sponge-like are 5, 10, and 20 wt.%. The samples were evaluated by optical microscopy (OM), scanning electron microscopy (SEM), density, Fourier transform infrared spectroscopy (FTIR), contact angle, Thermogravimetry, X-ray diffraction analysis (XRD), and compression strength test, respectively. FTIR results indicated that Pull was hydrogen-bonded to PU foam chains and increased the sponge-like scaffolds density, inducing a decrease in average cell size compared to the pristine PU, confirming that they act as nucleating agents. The Pull addition improved PU foams' hydrophobicity and mechanical properties and caused a thermal stability median between Pull and pristine PU. Thus, all renewable sponge-like scaffolds were hydrophobics and presented appropriate mechanical behavior, exhibiting better physicochemical properties, and appearing as promising candidates for biomedical applications.
Keywords: castor polyol-based polyurethane; pullulan; reactive filler; renewable scaffold; sponge-like